Restraint stress enhances alcohol intake in adolescent female rats but reduces alcohol intake in adolescent male and adult female rats. - Wille-Bille, Aranza; Ferreyra, Ana; Sciangula, Martina; Chiner, Florencia; Nizhnikov, Michael E; Pautassi, Ricardo Marcos (Behavioural brain research, 2017)
Adolescents may be more sensitive to stress-induced alcohol drinking than adults, which would explain the higher prevalence of alcohol abuse and dependence in late adolescence than in adulthood. The present study analyzed the impact of restraint stress on the initiation of alcohol intake across 2 weeks of intermittent, two-bottle choice intake in male and female adolescent rats and adult female rats. Restraint stress significantly increased alcohol intake and preference in female adolescent rats but decreased alcohol intake and preference in male adolescent and female adult rats. The effects of restraint stress on alcohol intake were mitigated in adolescent females following administration of the kappa opioid receptor antagonist norbinaltorphimine. Adolescent but not adult female rats that were subjected to restraint stress spent more time on the open arms of the elevated plus maze. Female adolescents exposed to stress also exhibited greater risk-taking behaviors in a concentric square field test compared with non-stressed controls. These results indicate age- and sex-related differences in the sensitivity to alcohol-stress interactions that may facilitate the initiation of alcohol use in female adolescents. The facilitatory effect of stress on alcohol intake was related to greater exploratory and risk-taking behaviors in young females after stress exposure. Copyright © 2017 Elsevier B.V. All rights reserved.
Keywords: *Aging/ph [Physiology]; *Aging/px [Psychology]; *Alcohol Drinking/pp [Physiopathology]; *Alcohol Drinking/px [Psychology]; *Sex Characteristics; *Stress, Psychological/pp [Physiopathology]; Adolescents; Adults; Age differences; Aging; Aging/de [Drug Effects]; Alcohol; Alcohol Drinking; Alcohol Drinking/dt [Drug Therapy]; Animals; Article; Central Nervous System Depressants; Central Nervous System Depressants/ad [Administration & Dosage]; Choice Behavior; Choice Behavior/de [Drug Effects]; Choice Behavior/ph [Physiology]; Disease Models, Animal; Ethanol; Ethanol/ad [Administration & Dosage]; Exploratory Behavior; Exploratory Behavior/de [Drug Effects]; Exploratory Behavior/ph [Physiology]; Female; Male; Motor Activity; Motor Activity/de [Drug Effects]; Motor Activity/ph [Physiology]; Naltrexone; Naltrexone/aa [Analogs & Derivatives]; Naltrexone/pd [Pharmacology]; Narcotic Antagonists; Narcotic Antagonists/pd [Pharmacology]; Rats, Wistar; Receptors, Opioid, kappa; Receptors, Opioid, kappa/ai [Antagonists & Inhibitors]; Receptors, Opioid, kappa/me [Metabolism]; Restraint, Physical; Risk-Taking; Sex Characteristics; Stress; Stress, Psychological; Stress, Psychological/dt [Drug Therapy]; Wistar rat; [kappa] opioid receptors; adolescent; adult; age; aging; alcohol; alcohol consumption; analogs and derivatives; animal; animal experiment; antagonists and inhibitors; behavior assessment; central depressant agent; comparative study; concentric square field test; controlled study; decision making; dept.psy; disease model; drinking behavior; drug effects; drug therapy; elevated plus maze test; exercise; experimental study; exploratory behavior; exploratory behavior test; female; high risk behavior; immobilization stress; kappa opiate receptor; kappa opiate receptor antagonist; male; mental stress; metabolism; motor activity; naltrexone; narcotic antagonist; nonhuman; norbinaltorphimine; pathophysiology; peer-reviewed; physiology; priority journal; psychology; rat; risk assessment; sensitivity analysis; sex difference; sexual characteristics; κ opioid receptors

Age-related effects of chronic restraint stress on ethanol drinking, ethanol-induced sedation, and on basal and stress-induced anxiety response. - Fernandez, Macarena Soledad; Fabio, Maria Carolina; Miranda-Morales, Roberto Sebastian; Virgolini, Miriam B; De Giovanni, Laura N; Hansen, Cristian; Wille-Bille, Aranza; Nizhnikov, Michael E; Spear, Linda P; Pautassi, Ricardo Marcos (Alcohol, 2016)
Adolescents are sensitive to the anxiolytic effect of ethanol, and evidence suggests that they may be more sensitive to stress than adults. Relatively little is known, however, about age-related differences in stress modulation of ethanol drinking or stress modulation of ethanol-induced sedation and hypnosis. We observed that chronic restraint stress transiently exacerbated free-choice ethanol drinking in adolescent, but not in adult, rats. Restraint stress altered exploration patterns of a light-dark box apparatus in adolescents and adults. Stressed animals spent significantly more time in the white area of the maze and made significantly more transfers between compartments than their non-stressed peers. Behavioral response to acute stress, on the other hand, was modulated by prior restraint stress only in adults. Adolescents, unlike adults, exhibited ethanol-induced motor stimulation in an open field. Stress increased the duration of loss of the righting reflex after a high ethanol dose, yet this effect was similar at both ages. Ethanol-induced sleep time was much higher in adult than in adolescent rats, yet stress diminished ethanol-induced sleep time only in adults. The study indicates age-related differences that may increase the risk for initiation and escalation in alcohol drinking. Copyright © 2016 Elsevier Inc. All rights reserved.
Keywords: *Alcohol Drinking/px [Psychology]; *Anxiety/px [Psychology]; *Ethanol/ad [Administration & Dosage]; *Hypnotics and Sedatives/ad [Administration & Dosage]; *Stress, Psychological/px [Psychology]; Adolescent; Adult; Age Factors; Alcohol Drinking; Alcohol Drinking/ae [Adverse Effects]; Alcohol Drinking/bl [Blood]; Animals; Anxiety; Anxiety/bl [Blood]; Anxiety/et [Etiology]; Article; Chronic Disease; Ethanol; Ethanol/to [Toxicity]; Hypnotics and Sedatives; Hypnotics and Sedatives/to [Toxicity]; Male; Rat; Rats; Rats, Sprague-Dawley; Rats, Wistar; Restraint stress; Sprague Dawley rat; Stress, Psychological; Stress, Psychological/bl [Blood]; Stress, Psychological/co [Complications]; Wistar rat; acute stress; adverse effects; age; age distribution; alcohol; alcohol blood level; alcohol consumption; animal; animal behavior; anxiety; blood; body weight; chronic disease; complication; controlled study; corticosterone; corticosterone blood level; dept.psy; drinking behavior; etiology; hypnosis; hypnotic sedative agent; locomotion; male; mental stress; motor activity; mouse; nonhuman; open field test; peer-reviewed; psychology; rat; restrain stress; righting reflex; sedation; sex difference; sleep time; stimulus response; stress